Flash‐Induced Stretchable Cu Conductor via Multiscale‐Interfacial Couplings. Issue 11 (4th October 2018) - Park, Jung Hwan; Seo, Jeongmin; Kim, Cheolgyu; Joe, Daniel J.; Lee, Han Eol; Im, Tae Hong; Seok, Jae Young; Jeong, Chang Kyu; Ma, Boo Soo; Park, Hyung Kun; Kim, Taek‐Soo; Lee, Keon Jae
Abstract: Herein, a novel stretchable Cu conductor with excellent conductivity and stretchability is reported via the flash‐induced multiscale tuning of Cu and an elastomer interface. Microscale randomly wrinkled Cu (amplitude of ≈5 µm and wavelength of ≈45 µm) is formed on a polymer substrate through a single pulse of a millisecond flash light, enabling the elongation of Cu to exceed 20% regardless of the stretching direction. The nanoscale interlocked interface between the Cu nanoparticles (NPs) and the elastomer increases the adhesion force of Cu, which contributes to a significant improvement of the Cu stability and stretchability under harsh yielding stress. Simultaneously, the flash‐induced photoreduction of CuO NPs and subsequent Cu NP welding lead to outstanding conductivity (≈37 kS cm −1 ) of the buckled elastic electrode. The 3D structure of randomly wrinkled Cu is modeled by finite element analysis simulations to show that the flash‐activated stretchable Cu conductors can endure strain over 20% in all directions. Finally, the wrinkled Cu is utilized for wireless near‐field communication on the skin of human wrist. Abstract : Flash‐induced stretchable copper (Cu) is developed by the photothermal multiscale interaction of the interface between Cu and an elastomer. Microscale randomly wrinkled Cu was formed on polymer via single‐pulsed millisecond flash, which enables omnidirectional elongation of Cu over 20%. Simultaneously, a nanoscale interlocked interface was structured between the Cu nanoparticles and the elastomer, significantly increasing the adhesion of the Cu.